Answers

2014-05-22T11:01:18+05:30
Solution :

 \frac{x+1}{x-1} + \frac{x-1}{x+1}
taking lcm

=  \frac{(x+1)(x+1)}{(x-1)(x+1)}  +  \frac{(x-1)(x-1)}{(x-1)(x+1)}

=  \frac{ (x+1)^{2} }{ x^{2} -1} + \frac{ (x-1)^{2} }{ x^{2} -1}

= \frac{ ( x^{2} +1+2x) + (x^{2} +1-2x)}{ x^{2} -1}

= {6(2 x^{2} + 2)} = 5( x^{2} -1)
12 x^{2} + 12 = 10 x^{2} -5
12 x^{2} -10 x^{2} =-12-5

=2 x^{2} =-17
=x= \sqrt{ \frac{-17}{2} }

1 1 1
no its wrong. its a quadratic equation and its answer is 6, 40/13. i need the solution
i made a mistake ans is root of +_(-17/7)
no dear, its not the right answer. anyways thanks a lot